Rescue Veno-Venous Extracorporeal Membrane Oxygenation for Aspiration-Induced Refractory Hypoxaemia Before Non-Deferrable Abdominal Surgery: A Case Report - Simon Dolenc; Primož Kastelic; Anja Kramarič Lozar; Primož Gradišek (Journal of Clinical Medicine, 2026)
Background: Pulmonary aspiration during induction of anaesthesia may lead to rapidly progressive, life-threatening hypoxaemic respiratory failure. This poses a particular challenge when urgent surgery cannot be deferred. Case Presentation: A 33-year-old man required urgent relaparotomy for mesenteric venous thrombosis and multifocal bowel gangrene after blunt abdominal trauma. During rapid-sequence induction, he aspirated approximately 230 mL of mixed liquid gastric contents and solid food particles. Despite immediate suctioning, three therapeutic bronchoscopies, volume-controlled ventilation with FiO2 1.0 and PEEP 10 cmH2O, stepwise PEEP titration, and inhaled nitric oxide, hypoxaemia progressed. At the final pre-ECMO assessment, SpO2 was 68%, pH 7.329, PaO2 5.1 kPa, PaCO2 6.66 kPa, and the PaO2/FiO2 ratio approximately 38 mmHg. Tidal volume was 590 mL (8.0 mL/kg of predicted body weight). Plateau pressure was not measured; driving pressure and pre-ECMO static compliance were therefore unavailable. Severe refractory hypoxaemia persisted for approximately 60 min. The decision to initiate VV-ECMO was made 45 min after aspiration; as a result, full femoro-jugular flow was achieved at 105 min after aspiration, and surgical incision followed 45 min later. The operation lasted 165 min. The estimated blood loss was 500 mL, and three units of packed red blood cells were transfused without uncontrolled surgical haemorrhage. The ECMO course was complicated by excessive advancement of the right internal jugular return cannula with clinically suspected recirculation and by marked transient thrombocytopenia. VV-ECMO was discontinued on ICU day 7, and final extubation occurred on ICU day 21. The patient was discharged home after regaining independence in basic activities of daily living, with an end-ileostomy and end-descending colostomy. Intestinal continuity was successfully restored at approximately 18 months. No formal pulmonary-function or neurocognitive testing was performed during follow-up. Conclusions: In this patient, rescue VV-ECMO provided gas-exchange support, enabling non-deferrable abdominal surgery to proceed. However, a single case cannot establish general feasibility, safety, effectiveness, optimal timing, or patient-selection criteria.